The Effect of Personality and Knowledge Sharing Toward Innovation Behavior of Employees - Nurhidayati, Nurhidayati; Sabrina, Mustika Nida (UNISSULA, 2023)
The purpose of this study was to determine the effect of agreeableness and openness to experience on innovation behavior through knowledge sharing. The population in this study were coffee shop workers in the city of Semarang which were estimated at 300 workers. The number of samples used 100 respondents with data collection using a questionnaire. The sampling method uses cluster random sampling. Analysis of the data used is descriptive analysis and Partial Least Square (PLS) analysis. The results revealed that agreeableness and openness to experience had a significant effect on knowledge sharing. Knowledge sharing positively influences innovation behavior and knowledge sharing can become an intervening variable (mediation) between agreeableness and openness to experience on innovation behavior.